Expressive Animated Character Sequences Using Knowledge-Based Painterly Rendering. (3rd November 2011) - Seifi, Hasti; DiPaola, Steve; Arya, Ali
Abstract : We propose a technique to enhance emotional expressiveness in games and animations. Artists have used colors and painting techniques to convey emotions in their paintings for many years. Moreover, researchers have found that colors and line properties affect users' emotions. We propose using painterly rendering for character sequences in games and animations with a knowledge-based approach. This technique is especially useful for parametric facial sequences. We introduce two parametric authoring tools for animation and painterly rendering and a method to integrate them into a knowledge-based painterly rendering system. Furthermore, we present the results of a preliminary study on using this technique for facial expressions in still images. The results of the study show the effect of different color palettes on the intensity perceived for an emotion by users. The proposed technique can provide the animator with a depiction tool to enhance the emotional content of a character sequence in games and animations.